2003
DOI: 10.1007/s10163-003-0095-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulverization of waste printed circuit boards

Abstract: A new pulverization method to reduce the volume of waste printed circuit boards is reported. About 50% of printed circuit boards with integrate circuits (ICs) could be pulverized by our method in one 20-min batch, but boards without ICs could not be pulverized. By repeating the process three times, about 95% of printed circuit boards with ICs could be made into a fine powder with particles less than 106 µm. A weight-drop test was also performed to examine the strength of the printed circuit boards and clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…As mentioned above, we previously reported that it is possible to perform fi ne pulverization of printed circuit boards with the chip components still attached at exceedingly high effi ciencies. 2 With regard to small chip parts, the concentration of precious metals is high and these parts are further miniaturized every year. In our process, we believe that pulverizing the printed circuit boards with the chip components still attached is a highly effective method for removing the small chip parts in particular.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, we previously reported that it is possible to perform fi ne pulverization of printed circuit boards with the chip components still attached at exceedingly high effi ciencies. 2 With regard to small chip parts, the concentration of precious metals is high and these parts are further miniaturized every year. In our process, we believe that pulverizing the printed circuit boards with the chip components still attached is a highly effective method for removing the small chip parts in particular.…”
Section: Resultsmentioning
confidence: 99%
“…2 The impact energy T (Ns), a relative value that indicates the degree of impact on the sample, was calculated using the following equation by setting the number of balls to B (units), the weight of a ball per unit to W (kg), and the ball acceleration rate to A (m/s 2 ):…”
Section: Pulverization and Separation Of The Printed Circuit Boardsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Therefore, a number of methods have been developed and applied for treatment of WPCBs; these include mechanical separation, biological recycling, crushing, hydrometallurgical and pyrometallurgical treatment, pulverization, plasma treatment, etc. [7][8][9][10][11][12][13] However, many of these methods have certain restrictions related to energy consumption, process efficiency, recovery yield or recycling rate, economic protability, pollution rate, and a limited focus on metals or non-metals recovery only. [14][15][16][17][18] These problems emerged as a result of the complexity of WPCB structure, which is comprised of berglass reinforced with resin and metal parts having a high hardness and tenacity.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a method for pelletizing and pulverizing waste PCBs together with the attached ICs to a powder with a grain size of less than 106 µm, which reduces the volume of waste and also allows recovery of the metals (3) . We found the powder contained about 400 ppm Ag, 220 ppm Pd, and 200 ppm Au.…”
Section: Introductionmentioning
confidence: 99%